Razlike v preživljanju prostega časa med študenti štirih držav - Kvesić, Mladen (Šport (Ljubljana), 2018)
The purpose of this research was to determine the difference of spending leisure time within teachers-to-be from different sociocultural and economic conditions. The sample included 415 students, from Bosnia and Herzegovina (61), Macedonia (128), Bulgaria (166) and Slovenia (60). The sample of variables consisted of a deliberately constructed questionnaire, divided into 4 sections (basic information, leisure options, the role of university and individual sports activity). Data were processed with descriptive statistics, comparative statistics, Anova (or Welchev test) and Games-Howell and Tukey HSD post hoc (in SPSS version 22). Every statistically significant conclusion was accepted at the risk level of 5%. (p <0.05). We found out that Slovenian students spend more time on learning as students of the other three countries. Students from all four countries spend about the same time in college. Slovenian students are more likely to work for survival, they are statistically significantly less frequent in discotheques and are more intensively engaged in sports activities than students from the other three countries. Students from all four countries want more focused offers for leisure activities; they point out the lack of sports competitions within the faculty (between the years), lack of camps and workshops for studying different skills, and the more frequent organization of sporting events.
Keywords: ekonomske razlike; leisure; prosti čas; socio-kulturne razlike; student; študent; študenti